New Tax Reporting via E-filing - Nada, Qatrun; Usrotin Choiriyah, Ilmi (Universitas Muhammadiyah Sidoarjo, 2022)
e-Filing is a tax reporting novelty that can be accessed more quickly with the internet network. But in reality e-Filing itself is still not widely spread. This is due to the lack of widespread socialization from the KPP Pratama. This study aims to find out and understand the novelty of tax reporting through e-Filing at the Pratama Tax Service Office of South Sidoarjo. The method used is descriptive qualitative method. The data obtained through interviews, observation, and documentation. The results of the study indicate that the novelty of Tax Reporting Services through e-Filing at KPP Pratama Sidoarjo Selatan in terms of innovation characteristics, namely having features and elements of novelty where with e-filing taxpayers can save time and costs, because e-filing can be accessed anytime and anywhere with internet facilities. The novelty of tax reporting through e-filing does not only benefit one party, but both parties, namely the taxpayer and also the South Sidoarjo KPP Pratama which can save storage space and paper.